2013
DOI: 10.1016/j.rmed.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to inhaled therapies, health outcomes and costs in patients with asthma and COPD

Abstract: Suboptimal adherence to pharmacological treatment of asthma and chronic obstructive pulmonary disease (COPD) has adverse effects on disease control and treatment costs. The reasons behind non-adherence revolve around patient knowledge/education, inhaler device convenience and satisfaction, age, adverse effects and medication costs. Age is of particular concern given the increasing prevalence of asthma in the young and increased rates of non-adherence in adolescents compared with children and adults. The correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
288
2
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(316 citation statements)
references
References 91 publications
13
288
2
13
Order By: Relevance
“…HCP should repeat this instructions at subsequent visits to confirm correct usage of inhaler device (29,30). Another critical step is the way of the education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCP should repeat this instructions at subsequent visits to confirm correct usage of inhaler device (29,30). Another critical step is the way of the education.…”
Section: Resultsmentioning
confidence: 99%
“…People with asthma and improper inhaler technique were shown to have poorer symptom control compared to those with good inhaler technique, with a subsequent increase in medical or emergency visits (8,11,20,25). Furthermore, as improved inhalation technique has been shown to improve adherence to asthma therapy (possibly due to the positive reinforcing effects of improved symptom relief concurrent with improved medication administration (29).…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, around 60% of COPD patients had poor adherence to their inhalation therapy [14,15]. A recent review reported a wide variation in adherence rates for asthma and COPD patients ranging from 22% to 78% [16]. Regarding IT, evidence from Europe shows that up to 50% of patients fail to use their inhalers correctly [17].…”
Section: One Of the Main Objectives Of The Global Initiative For Chromentioning
confidence: 99%
“…Asthma and chronic obstructive pulmonary disease (COPD) are two of the leading causes of morbidity, mortality and economic burden worldwide [1]. Epidemiological data of Asthma in Greece are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic respiratory diseases represent 5% of total disease burden and 8.3% of chronic disease burden worldwide, accounting for more than 4 million deaths each year [1]. COPD is a leading cause of morbidity and mortality worldwide [4] and results in an economic and social burden which is substantial and increasing.…”
Section: Introductionmentioning
confidence: 99%